Comprehensive Review On Controller For Leader-Follower Robotic System - Ab Rashid, Mohd Zamzuri; Mohd Yakub, Mohd Fitri; Shaikh Salim, Sheikh Ahmad Zaki; Ali Mat, Mohamed Sukri; Mamat, Normaisharah M.; Mohd Putra, S. M. S.; Roslan, Shairatul Amni Husna; Mohd Shah, Hairol Nizam; Mohd Aras, Mohd Shahrieel (National Institute Of Science Communication And Information Resources (NISCAIR), 2019)
This paper presents a comprehensive review of the leader-follower robotics system. The aim of this paper is to find and elaborate on the current trends in the swarm robotic system, leader-follower, and multi-agent system. Another part of this review will focus on finding the trend of controller utilized by previous researchers in the leader-follower system. The controller that is commonly applied by the researchers is mostly adaptive and non-linear controllers. The paper also explores the subject of study or system used during the research which normally employs multi-robot, multi-agent, space flying, reconfigurable system, multi-legs system or unmanned system. Another aspect of this paper concentrates on the topology employed by the researchers when they conducted simulation or experimental studies.